The Verbal Influence of Husband and Wife on The Verbal of Couple and Children in The Family - Defina, Defina (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Interaction among family members can be in the form of verbal interaction. A bad verbal partner has an impact on verbal in the family. The purpose of this study was to examine the relationship and test the influence of family characteristics, husband-wife verbal, on partner and child verbal. This study used a cross-sectional design. The population of this research is husband/wife in Indonesia. The number of respondents was 113 people. The results show that the income of one husband and wife has a significant positive relationship with verbal affection for their partner and their children. Verbal violence of one partner has a significant positive relationship with verbal abuse of their children. A husband/wife's verbal affection for a partner has a significant positive relationship with verbal affection for children. Respondents' verbal violence to their partners had a significant positive effect on verbal violence toward children. Respondents' verbal affection for their partner has a significant positive effect on verbal affection for children. The negative diction used is stupid, and the positive meaning is dear. In conclusion, husband/wife's verbal relationship and influence on their verbal to their children.